#TITLE_ALTERNATIVE# - WAHYUNINGRUM (NIM 30504013), DEANA
Corrosion is one of major problems in oil and gas industries all over the world, which causes great loss economically and environmentally. The studies concerning corrosion prevention have been carried out since 1940s, where imidazole derivative compounds held important rule as corrosion inhibitor. The various functional groups and their position on imidazole structure used as corrosion inhibitor are limited and still need to be improved. Therefore the study concerning the variation and modification of functional groups on imidazole structures should be developed to study their corrosion inhibition mechanism on carbon steel. Based on many reported studies, the organic compounds, which have potent as corrosion inhibitors, are hydrophobic heterocyclic compounds having aromatic and/or aliphatic substituents. The objectives of this research is to synthesize some hydrophobic imidazole derivative compounds substituted with aliphatic and/or aromatics that are potential as corrosion inhibitor, and to determine their corrosion inhibition activities toward carbon steel. The data collected from the corrosion inhibition activities study was analyzed to obtain some thermodynamic parameters needed to study the corrosion inhibition mechanism of imidazole derivatives compounds. The novel contribution of this research is the development and modification of various supported phases to synthesize imidazole compounds utilizing microwave assisted organic synthesis (MAOS) method. Furthermore, the discussion about corrosion inhibition mechanism of 4,5-diphenylimidazole derivative compounds and 1-benzyl-2-phenylbenzimidazole, as well as the relationship between structure and their corrosion inhibition activities became the strong point of this research, because so far the study of corrosion inhibition mechanism of this group have not been endeavored before. The 4,5-diphenylimidazole was chosen as corrosion inhibitor model, since it has been reported that the presence of phenyl groups attached to imidazole ring would increase its corrosion inhibition activity. Azocine heptadecyl/heptadecenyl substituted compounds were also synthesized as reference molecules, since these compounds have similar structure with oleic imidazoline that have been widely and commercially used in oil and gas industries. In this study, 19 (nineteen) compounds have been synthesized utilizing conventional (reflux) and MAOS method, which were unsubstituted imidazole, twelve 4,5-diphenylimidazole derivatives, three benzimidazole derivatives, and three azocine derivatives. The MAOS method showed advantages in shorter reaction times (50ÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚Â‚ÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â–100 times) and higher chemical yields (1,5ÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚Â‚ÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â–10% times) compared to the conventional one. The structure characterization of synthesized products utilized mass spectrophotometer, infrared, and nuclear magnetic resonance spectroscopy. The synthesized imidazole derivatives were: 1Himidazole, 4,5-diphenyl-1H-imidazole, 2-ethyl-4,5-diphenyl-1H-imidazole, 2-hexyl-4,5-diphenyl-1H-imidazole, 2,4,5-triphenyl-1H-imidazole, 2-(4-methoxyphenyl)-4,5-diphenyl-1H-imidazole, 1-(2-methyl-4,5-diphenyl-1Himidazole-1-il)ethanol, (E)-2-ethyl-4,5-diphenyl-1-(prop-1-enil)-1H-imidazole, (E)-1-(hept-1-enyl)-2-hexyl-4,5-diphenyl-1H-imidazol, 2-hexyl-4,5-diphenyl-1-vinyl-1H-imidazole, 2,4,5-triphenyl-1-vinyl-1H-imidazole, 2-(4-methoxyphenyl)-4,5-diphenyl-1-vinyl-1H-imidazole, (E)-N-ethylidene-1-(2-hexyl-4,5-diphenyl-1H-imidazole-1-yl)propan-2-amine, benzimidazole, 1-benzyl-2-phenyl-1H-1,3-benzimidazole, 2-phenyl-1H-1,3-benzimidazole, (Z)-2-((Z)-heptadec-8-enyl)-1,4,5,6,7,8-hexahydro-1,3,6-triazocine, (Z)-2-((Z)-heptadec-8-enyl)-5,6,7,8-tetrahydro-4H-1,3,6-oxadiazocine and (Z)-2-heptadecyl-1,4,5,6,7,8-hexahydro-1,3,6-triazocine. The corrosion inhibition activities determination of synthesized products utilized Tafel method in 1% (w/v) NaCl solution. As comparison, the corrosion inhibition activities determination also utilized EIS (Electrochemical Impedance Spectroscopy) method. The comparison between data from Tafel and EIS method showed the correlated value of corrosion inhibition activities of imidazole derivatives. The relationship between structure of synthesized imidazole derivatives and their corrosion inhibition activities analysis showed that the high electron density, the presence of electron donating group, the elongation of phi (π) electron resonance within imidazole aromatic rings, the imines (-C=N) group, and the planarity of structure are the factors cause the improvement of corrosion inhibition activity. The high electron density within imidazole derivatives structure is needed to improve the adsorption capacity on carbon steel surface. The presences of electron withdrawing groups and steric effect of bulky substituents on imidazole structure are the factors cause the decrease in corrosion inhibition activity. The increase in concentration of imidazole derivative compound in 1% (w/v) NaCl solution tends to increase its corrosion inhibition activity to an optimum extent. The determination of adsorption free Gibbs energy (ΔG0 ads) by the analysis of Langmuir and Temkin adsorption isotherms, as well as the determination of activation energy, Ea, and activated state free Gibbs energy, ΔG*, have the close relationship that strengthen the hypothesis concerning the potent of the synthesized imidazole derivatives as corrosion inhibitor towards carbon steel in 1% (w/v) NaCl solution through the adsorption mechanism process on carbon steel surface. All of the ΔG0 ads value of each synthesized imidazole derivatives is negative, whereas the value of Ea and ΔG* are positives, indicating that the synthesized compounds have the potent to inhibit the corrosion process of carbon steel through the monolayer formation on metal surface, via semiphysiosorption and/or semi-chemisorptions. In conclusion, all of synthesized imidazole derivatives are potential as corrosion inhibitors toward carbon steel.